MONETARY POLICY SHOCKS AND ISLAMIC BANKS DEPOSITS IN INDONESIAN DUAL BANKING SYSTEM AFTER THE FINANCIAL CRISIS - Ahmad Affandi; Luqyan Tamanni (University of Merdeka Malang, 2010)
Use of riba (usury) in the economic system remained a key factor that led to financial crisis since theinception of modern economy in the late of 17th century. Implementation of interest based monetary policystipulated rampant speculation as common practices in the global financial sector. Although Islamic bankingwas governed by syariah (Divine Law), which was assumed to be resilient from distress, the volatility ofinterest movement would generally affect Islamic banks operations in a dual banking system. This paperwould look at this issue and would empirically explore the dynamic inter-relationships between deposits ofIslamic banks with monetary policy variables in Indonesia. In terms of market share, as of 2009, Islamicbanking asset in Indonesia was a meager 2%. The industry had been affected by few monetary policy shockson its deposits and financing. The study would employ vector auto regression model (VAR) to explore thedynamics between the variables. The study would focus on data from 2004 to 2008 or performance after theAsian financial crisis. The results from these tests determined that shariah based deposits played significantrole in transmitting monetary policy effects to the economy. This study found that Islamic banking depositsin Indonesia were not sensitive to monetary policy changes. This study also concluded that IndonesianIslamic banks were resilient to financial crisis.